The Influence of Perceived Ease of Use, Perceived Trust, and Perceived Benefits on Unismuh makassar Students' Interest in Using E-Money (OVO) on the Grab Application - Agusdiwana Suarni; Mahmud Nuhung; Muh Fadhil (Jurnal Ilmu Manajemen Profitability, 2024)
This research aims to determine the influence of perceived Ease of Use, Trust, and Benefits on the interest of Unismuh students in using the e-money (OVO) Grab application. This study employs a quantitative approach, utilizing a census method sample of 80 respondents. The data analysis was conducted using multiple linear regression analysis processed with SPSS Version 25. The research findings indicate that perceived Ease of Use significantly and positively impacts student interest. However, the influence of perceived Trust, while positive, does not significantly affect student interest. Conversely, the perceived Benefits significantly and positively impact the interest of Unismuh students in using the OVO Grab application. In summary, the study reveals that while both Ease of Use and Benefits perceptions play crucial roles in driving student interest in the OVO Grab application, Trust perception alone does not have a significant effect. These insights can guide improvements in the application’s design and functionality, enhancing user engagement and satisfaction.